PENGARUH LEVERAGE DAN CAPITAL INTENSITY RATIO TERHADAP EFFECTIVE TAX RATE DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di BEI Periode 2016-2020) - Rianto; Muhamad Alfian (RELEVAN : Jurnal Riset Akuntansi, 2022)
This study aims to examine the effect of leverage and capital intensity ratio on the effective tax rate with profitability as a moderator of mining sector companies listed on the Indonesia Stock Exchange in 2016-2020. The population of this study includes all mining sector companies during the 2016-2020 period. Samples were taken using purposive sampling method with certain criteria, during the research period. Based on the criteria that have been determined using panel data, the amount of data that can be processed is 70 data. The analytical method used is panel data regression and moderated regression analysis which is processed using Eviews 10. The results of this study indicate that: (1) Leverage has a positive effect on the Effective tax rate; (2) Capital intensity ratio has no effect on the Effective tax rate; (3) Leverage moderated through Profitability weakens the effect on the Effective tax rate; (4) Capital intensity ratio moderated through Profitability has no effect on the Effective tax rate